Socio-Ecological Outcomes of Single-Species Fisheries Management: The Case of Yellow Perch in Lake Erie - Lee, Katherine; Apriesnig, Jenny; Zhang, Hongyan (Frontiers in Ecology and Evolution, 2021)
This paper uses seminal models in fisheries economics to assess the ecosystem effects of policy focused on sustainable management of a single fish stock. Economic models representing fishing decisions under open access and two fisheries management schemes are parameterized using data from the four management units in the Lake Erie Yellow Perch (Persus flavenscens) fishery and linked with an end-to-end ecosystem model representative of the lake food web and spatial species interactions. We find that the sustainable harvest rules from single species economic models result in significant changes to biomass of species in planktivorous, omnivorous, and piscivorous groups in the ecosystem model. These impacts can be traced through the food web back to harvest rules implemented in the management units. Most notably, the biomass of several non-target but also commercially harvested fish species are reduced through Yellow Perch fishing. In some cases, the economic losses to coexisting fisheries exceeds benefits gained from implementing the Yellow Perch management scheme. Our results imply that while an ecosystem-based approach to fisheries management requires weighing trade-offs between multiple fisheries, an ex ante understanding of the whole-system consequences of harvest rules can be critical for developing policy that overall enhances ecological and social wellbeing.